Integrating Indigenous Wisdom in Environmental Protection: Exploring Village Authority within the Framework of State Responsibility in Indonesia - Permana, Deni Yusup; Imamulhadi, Imamulhadi; Idris, Idris; Mariana, Montisa (Jambura Law Review, 2025)
Environmental management in Indonesia faces significant challenges, including land conversion, pollution, and ecosystem degradation. These issues are primarily driven by human activities and a lack of integration between state policies and local wisdom. Indigenous peoples, who possess traditional knowledge and wisdom-based management systems, play a crucial role in environmental conservation. However, there are still gaps in the recognition of their rights regarding natural resource management. This research aims to analyze the role of local wisdom in environmental management within the framework of village authority and state responsibility. The methodology employed is descriptive analytical, utilizing a normative juridical approach that combines literature review and interviews with indigenous communities in Bali, Jambi, West Sumatra, and Papua. The findings indicate that while local wisdom values, such as Tri Hita Karana in Bali and arat sabulungan in Mentawai, significantly contribute to ecosystem maintenance, the integration between government policies and village authority remains limited. This research proposes strengthening the synergy between local wisdom and state policy to develop an inclusive and sustainable environmental management model. The novelty of this study lies in mapping the contributions of local wisdom within the context of village authority and highlighting the urgency for policy revisions to enhance the active role of indigenous peoples in environmental conservation.